Recent Advances in Nonlinear Dynamics and Synchronization With Selected Applications in Electrical Engineering, Neurocomputing, and Transportation - Kyamakya, Kyandoghere; Mathis, Wolfgang; Stoop, Ruedi; Chedjou, Jean Chamberlain; Li, Zhong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book focuses on modelling and simulation, control and optimization, signal processing, and forecasting in selected nonlinear dynamical systems, presenting both literature reviews and novel concepts.   It develops analytical or numerical approaches, which are simple to use, robust, stable, flexible and universally applicable to the analysis of complex nonlinear dynamical systems. As such it addresses key challenges are addressed, e.g. efficient handling of time-varying dynamics, efficient design, faster numerical computations, robustness, stability and convergence of algorithms.   The book provides a series of contributions discussing either the design or analysis of complex systems in sciences and engineering, and the concepts developed involve nonlinear dynamics, synchronization, optimization, machine learning, and forecasting. Both theoretical and practical aspects of diverse areas are investigated, specifically neurocomputi ng,transportation engineering, theoretical electrical engineering, signal processing, communications engineering, and computational intelligence.   It is a valuable resource for students and researchers interested in nonlinear dynamics and synchronization with applications in selected areas.
On the Construction of Dissipative Polynomial Nambu Systems with Limit Cycles -- On the dynamics of chaotic systems with multiple attractors: A case study -- Multivaluedness Aspects in Self-organization, Complexity and Computations Investigations by Strong Anticipation -- A Review of Traffic Light Control Systems and Introduction of a Control Concept Based on Coupled Nonlinear Oscillators -- Neural network based calibration of macroscopic traffic flow models -- Travelers of the second modernity: where technological and social dynamic complexity meet each other -- Design of a Chaotic Pulse-Position Modulation Circuit -- Emotion Recognition involving Physiological and Speech Signals: A Comprehensive Review -- Neurocomputing-based Matrix Inversion: A critical Review of the related State-of-the-Art.
Keywords: Dynamics; Nonlinear theories; Nonlinear Optics; Electrical engineering; Transportation engineering; Traffic engineering; Computational intelligence; Applied Dynamical Systems; Nonlinear Optics; Electrical and Electronic Engineering; Transportation Technology and Traffic Engineering; Computational Intelligence